High Blood Pressure and All-Cause and Cardiovascular Disease Mortalities in Community-Dwelling Older Adults. Issue 47 (November 2015) - Wu, Chen-Yi; Hu, Hsiao-Yun; Chou, Yiing-Jenq; Huang, Nicole; Chou, Yi-Chang; Li, Chung-Pin
Abstract : Abstract: Although hypertension is common among older adults, the optimal blood pressure (BP) for survival in older adults remains unclear. We attempt to use a large cohort to assess the relationship between BP and mortality and to gain insight into what level of BP is required for optimal survival in older adults. A total of 77, 389 community-dwelling adults, aged ≥65 years, were followed between 2006 and 2010. Mortality was determined using matching cohort identifications with national death files. Cox proportional hazards regression models were used to evaluate the relationship of BP with all-cause, cardiovascular disease (CVD), and expanded-CVD mortalities. The mortality risks of the stage 2–3 hypertension group were substantial (all-cause mortality: hazard ratio [HR]: 1.23; 95% confidence interval [CI]: 1.10–1.37; CVDs mortality: HR: 1.31; 95% CI: 1.05–1.64; expanded-CVDs mortality: HR: 1.40; 95% CI: 1.15–1.71). The cardiovascular and expanded-cardiovascular mortality risks were lowest when systolic blood pressures were 120 to 129 mm Hg, and increased significantly when systolic blood pressures (SBPs) were ≥160 mm Hg or diastolic BPs were ≥90 mm Hg. A J-curve phenomenon for SBP on CVD and expanded-CVD mortality was observed. The impacts of stage 2–3 hypertension on mortality risks were significantly increased among women. The mortality risks of hypertension were not attenuated with older age. This study provides insight for identifying the optimal BP for survival in older adults, and extends the knowledge of the impacts of hypertension on mortality risks among women and the older adults. Abstract : Supplemental Digital Content is available in the text